2007
DOI: 10.1002/app.26105
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of photoinduced birefringence in the guest–host system of poly(methyl methacrylate) doped with azobenzene‐containing crown ethers

Abstract: The kinetics of the buildup and decay of photoinduced birefringence was examined in a series of host-guest systems: azobenzene-containing crown ethers, differing in the size of the crowns, dissolved in a poly (methyl methacrylate) matrix. In all samples, the kinetics of the buildup of the birefringence was reasonably described by a sum of two exponential functions, the time constants being inversely proportional to the intensity of the pumping light and the magnitudes of the signals at the saturation level dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Our results are similar to those found for other azo‐modified polymers9–20 but different from those in a system based on a natural polymer host: a DNA‐CTMA (hexadecyltrimethyl‐ammonium chloride) system with disperse red 1 azo dye (DR1) partially intercalated. In the latter case, the response times for similar intensity levels were in the millisecond range, but the diffraction efficiencies were much less: of the order of 0.005% 29, 30…”
Section: Holographysupporting
confidence: 69%
See 1 more Smart Citation
“…Our results are similar to those found for other azo‐modified polymers9–20 but different from those in a system based on a natural polymer host: a DNA‐CTMA (hexadecyltrimethyl‐ammonium chloride) system with disperse red 1 azo dye (DR1) partially intercalated. In the latter case, the response times for similar intensity levels were in the millisecond range, but the diffraction efficiencies were much less: of the order of 0.005% 29, 30…”
Section: Holographysupporting
confidence: 69%
“…We show here that these azo‐modified silks have nonlinear optical properties similar to those that have been extensively studied in the past in other azo‐modified polymers. These effects include optically induced birefringence,9–12 holographic recording,13, 14 and optically induced surface relief gratings 15–20. Potential applications extending these approaches to silk include optical patterning of tissue engineering scaffolds, optical switching of biomaterial response, sensing, and optically controlled drug release.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of the buildup and decay of photoinduced birefringence of crown ethers with inherent azo groups 21 – 24 (Fig. 16 a) of different size of the macrocyle was investigated in poly(methyl methacrylate) matrix [ 154 ]. For all cases it was found that the kinetics of the buildup of the birefringence was suitably described by a sum of two exponential functions, the time constants (being function of the pumping light characteristic) and sample thickness.…”
Section: Crown Ethers With Azobenzene Moiety(-ies)mentioning
confidence: 99%
“…The optical anisotropy occurring in photo-responsive, nonlinear chromophores in polymer matrices has been investigated in various host-guest systems, and most of these studies emphasized a complex dynamics characterizing both the buildup and the decay regimes. 27,[34][35][36][37][38] A bi-exponential function is often used to account for the temporal evolution of the observed rise and decay of optical nonlinearities. 27,36 More specifically, for the relaxation process occurring when light is turned off, the fast component is attributed to thermodynamically-activated cis-to-trans conformational changes, while the slow one originates from angular re-distribution of the trans isomers, and the mobility and relaxation of the polymer chains of the host.…”
Section: Resultsmentioning
confidence: 99%
“…27,[34][35][36][37][38] A bi-exponential function is often used to account for the temporal evolution of the observed rise and decay of optical nonlinearities. 27,36 More specifically, for the relaxation process occurring when light is turned off, the fast component is attributed to thermodynamically-activated cis-to-trans conformational changes, while the slow one originates from angular re-distribution of the trans isomers, and the mobility and relaxation of the polymer chains of the host. In other works, 37,38 a stretched exponential function was found to describe the dynamics of the photoinduced nonlinear properties, and a tight relationship between the mechanical/rheological properties of the polymeric hosts and the temporal evolution of the photo-induced alignment of the guest molecules was also evidenced.…”
Section: Resultsmentioning
confidence: 99%